2016
DOI: 10.21615/cesmvz.11.2.2
|View full text |Cite
|
Sign up to set email alerts
|

Balance de nitrógeno, fósforo y potasio en vacas Holstein pastando praderas de kikuyo (Cenchrus clandestinus) en el norte de Antioquia

Abstract: To aim to estimate the balance of nitrogen (N), phosphorus (P) and potassium (K) in Holstein cows in northern Antioquia in the three thirds of lactation and in two seasons (high and low precipitation) grazing kikuyo grass (Cenchrus clandestinus), nine cows (three by lactation third) of five herds to which they estimated forage intake, consumption of food supplements and mineralized salt, were selected and were estimated excretion of feces, urine and milk secretion during last three days of an experimental peri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
1
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 36 publications
(49 reference statements)
0
1
0
3
Order By: Relevance
“…This is more critical as the proportion of nitrogen in animal urine has increased with increasing nitrogen intake; although it has remained relatively constant in feces (Jarvis et al, 1995). According to Jaimes and Correa (2016) the efficiency in the use of N by lactating cows varies between 8.96 and 27.82% in Colombia, which, according to the number of animals per unit area can generate the application of up to 374 kg of N/ha/yr from manure (Correa et al, 2012). Likewise, Rivera et al (2018) found that cows excreted 72% of ingested nitrogen in tropical dairy systems, generating the deposition of 46.8 kg N/animal/yr from manure and 42.9 kg from urine when the diet had on average 14% crude protein (CP).…”
Section: Nitrous Oxide and Methane Emissions In Grazin Systems Nitrous Oxide Emissionsmentioning
confidence: 99%
“…This is more critical as the proportion of nitrogen in animal urine has increased with increasing nitrogen intake; although it has remained relatively constant in feces (Jarvis et al, 1995). According to Jaimes and Correa (2016) the efficiency in the use of N by lactating cows varies between 8.96 and 27.82% in Colombia, which, according to the number of animals per unit area can generate the application of up to 374 kg of N/ha/yr from manure (Correa et al, 2012). Likewise, Rivera et al (2018) found that cows excreted 72% of ingested nitrogen in tropical dairy systems, generating the deposition of 46.8 kg N/animal/yr from manure and 42.9 kg from urine when the diet had on average 14% crude protein (CP).…”
Section: Nitrous Oxide and Methane Emissions In Grazin Systems Nitrous Oxide Emissionsmentioning
confidence: 99%
“…En ámbito lechero, se visualiza todo un sistema de tradición cultural en aspectos teóricos y empíricos, donde se hace evidente que pocas personas son las idóneas para llevar a cabo decisiones cruciales y propias de la ganadería lechera, en particular, en lo que respecta al tratamiento de los suelos y praderas muchas veces se queda limitado a las condiciones geográficas y climatológicas [10,11].…”
Section: Componente Interno Cunclassified
“…En la mayoría de los casos, la excreción de nutrientes por parte del animal supera las necesidades de las plantas. Para el norte de Antioquia, la excreción de N fluctúa entre 523 y 1130 kg/ha/año (Jaimes y Correa, 2016), dependiendo de la carga animal; mientras que la demanda de N de los principales recursos forrajeros de la zona corresponde a 500 kg/ha/año. Esto contribuye con la lixiviación de nutrientes y la producción de CH4, CO2 y, principalmente, de N2O.…”
Section: Introductionunclassified